Diagnostic laparoscopy in pre‐surgical planning for higher stage endometriosis: Is it still relevant?. (28th July 2016) - Menakaya, Uche A.; Rombauts, Luk; Johnson, Neil P.
Abstract : It has become necessary to re ‐ examine the relevance of diagnostic laparoscopy in the two‐stage approach to surgical management of symptomatic women with higher stage endometriosis following emerging evidence demonstrating acceptable diagnostic performance of alternative less invasive and less expensive imaging modalities. We highlight the relative merits of these presurgical diagnostic imaging modalities and propose strategies that address the challenge of transitioning to a new diagnostic paradigm in the management of symptomatic women with higher stage endometriosis.